Actions of the Manufacturers of Herbal and Other High-Demand Medicinal Products According to the EAEU Authorisation Procedures: Practical Recommendations - E. M. Rychikhina (Регуляторные исследования и экспертиза лекарственных средств, 2024)
This article covers procedures for transitioning to the common market of the Eurasian Economic Union (EAEU), with a focus on low-margin yet high-demand medicines, including herbal medicinal products. First, the article analyses applicant engagement in aligning the dossiers for nationally authorised medicinal products with the requirements of the EAEU authorisation procedures. Then, the article describes the legislative  changes  introduced  to  ease  authorisation  requirements.  Finally, the author provides recommendations for applicants.